Effect of Backpack Load on Gait Speed During Walking among University Student: A Pilot Study - Susilo, Taufik Eko (FISIO MU: Physiotherapy Evidences, 2023)
Nowdays, the backpack is designed multipurpose to carry all human needs. However, the excessive load on the backpack could lead to the postural problem that disturbs the human activities. People carry various loads of backpack in different positions every day and it tends to significant changes in physical performances such as walking speed and cadence . Carrying backpacks can cause the undesired posture which in turns can cause muscle fatigue, back pain, and spinal deformity eventually for the severity case. Standing and walking with backpacks may affect both static and dynamic balances which induce postural instability. Purpose: To identify the effect of 10% backpack load on gait speed during walking among university students Methodology: This observational study used repetitive experimental measured. Results: in backpack load comparison in the 10-meter walkway, the gait speed was significantly different between walking with and without load (p< 0.001). In 3-meter gait speed, there were significant different speed among normal, fast, and slow gait in each walking condition, with and without backpack load (p <0.05), respectively. For pos-hoc analysis, there were significantly different in normal and fast gait speed (p = 0.001), and fast and slow gait speed (p = 0.007), but there were significant differences of normal and slow gait speed (p = 0.314) in walking 3m without backpack load. Then, there were significantly different in normal and fast gait speed (p = 0.007), and normal and slow gait speed (p = 0.038), but there were significant differences of fast and slow gait speed (p = 0.445) in walking 3m with backpack load. Applications/Originality/Value: this study was the pilot study that tested the gait speed among university student who uses the backpack Keywords: backpack, load, gait speed